Response of alfalfa (Medicago sativa L.) to single and mixed inoculation with phosphate-solubilizing bacteria and Sinorhizobium meliloti - Guiñazú, Lorena Belén (2010)
The objectives of this work were to phenotypically and genetically characterize alfalfa rhizosphere bacteria and to evaluate the effect of single or mixed inoculation upon nodulation and biological nitrogen fixation. Thirty-two strains showed tricalcium phosphate solubilization ability, and two of them caused bigger or equal solubilization halos than the control strain P. putida SP22. The comparison of the 16S ribosomal DNA sequences indicated that these strains are phylogenetically related to Bacillus spp. and Pseudomonas spp. A beneficial effect of both isolates on alfalfa growth was observed in coinoculation assays. Pseudomonas sp. FM7d caused a significant increase in root and shoot dry weight, length, and surface area of roots, number, and symbiotic properties of alfalfa plants. The plants coinoculated with Sinorhizobium meliloti B399 and the Bacillus sp. M7c showed significant increases in the measured parameters. Our results indicating that strains Pseudomonas sp. FM7d and Bacillus sp. M7c can be considered for the formulation of new inoculants.